2019
DOI: 10.4314/ahs.v19i3.23
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 variants C3435T and T129C are not associated with colorectal cancer risk

Abstract: Background: Colorectal cancer (CRC) is one of the most prevalent cancers in Saudi Arabia that is highly characterized with poor survival rate and advanced metastasis. Many studies contribute this poor outcome to the expression of ABC transporters on the surface of cancer cells.Objectives: In this study, two ABCB1 variants, C3435T and T129C, were examined to evaluate their contribution to CRC risk.Methods: 125 subjects (62 CRC patients and 63 healthy controls) were involved. The DNA was isolated and analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Zamzam Water: The Prophet PBUH said, "The water of Zamzam is good for whatever it is drunk for," (Ibn Majah: 3062). Several studies found that Zamzam water showed cytotoxicity and anticancer effects against human colon, breast, lung, and uterine cancer cell lines (Abd-Rabou et al, 2018;Al Zahrani et al, 2019;Omar et al, 2017). 6.…”
Section: Tawakkul (Reliance On God)mentioning
confidence: 99%
“…Zamzam Water: The Prophet PBUH said, "The water of Zamzam is good for whatever it is drunk for," (Ibn Majah: 3062). Several studies found that Zamzam water showed cytotoxicity and anticancer effects against human colon, breast, lung, and uterine cancer cell lines (Abd-Rabou et al, 2018;Al Zahrani et al, 2019;Omar et al, 2017). 6.…”
Section: Tawakkul (Reliance On God)mentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Protective variants that have been found in the Saudi population include ABCB1 G2677T, ADIPOQ T45G, CTNNB1 rs44135385, rs2284396, CYP19A1 rs4774585, rs936308, rs4775936, IL7R rs1053496, LRP6 rs2284396, PARP1 rs8679, SFRP3 rs7775, TDG rs1866074, TLR4 rs10759931 and rs2770150, TLR9 rs187084 and rs352144, VDR1BsmI rs1544410 )Table 2(. 41,[50][51][52][53][54][55][56][57][58][59][60][61] Sporadic CRC. It develops through 3 genetic pathways: CIN pathway )70-85% of sporadic CRC(, MSI pathway )10-15%(, and the CpG island methylation pathway )CIMP, <5%(.…”
Section: (mentioning
confidence: 99%